Sarcomatoid Renal Cell Carcinoma in an Adolescent with Sickle Cell Anaemia - H. R. Ahmad; J. A. Faruk; M. A. Bugaje; A. Solomon; M. O. A. Samaila; R. M. Akuse (Case Reports in Oncological Medicine)
Malignancies have been reported to occur in people with sickle cell disease. Renal medullary carcinoma (RMC), also tagged seventh sickle cell nephropathy, is an aggressive cancer seen almost exclusively in people with sickle cell disease with more than 160 cases reported worldwide, but only few cases were reported in patients with sickle cell anaemia (HBSS) and from Nigeria. Sarcomatoid renal cell carcinoma is a renal tumour of any histologic variant containing foci of high-grade malignant spindle cells. We report an adolescent girl with sickle cell anaemia (HBSS) who presented with left renal tumour, histology of which confirmed a diagnosis of sarcomatoid renal cell carcinoma (sRCC). Surgical debulking and palliative care with chemotherapy were given, and she demised 10 months after. The rarity of the case and challenges of managing a cancer in the background of a chronic haematologic disorder are highlighted.